Oligomeric Proanthocyanidins Counteracts the Negative Effects of High Level of Dietary Histamine on American Eel (Anguilla rostrata) - Zhai, Shaowei; Wang, Yue; He, Yingxia; Chen, Xuehao (Frontiers in Marine Science, 2020)
The economic loss of intestinal inflammation by histamine in diet has caused concern in eel culture, it is urgent to develop a natural feed additive to alleviate the negative effects of high level of dietary histamine. Oligomeric proanthocyanidins (OPC), as the natural antioxidant to scavenge free radicals, was supplemented to alleviate the effects of dietary histamine on parameters of growth, serum biochemistry and liver metabolites of juvenile American eels in present study. The juvenile American eel with an initial body weight of (10.84±0.16 g/fish) were divided into control group fed commercial diet, HIS group fed commercial diet supplemented 300 mg/kg histamine, and OPC group fed commercial diet supplemented 300 mg/kg histamine and 300 mg/kg OPC. Trial period was 11 weeks. Compared with HIS group, dietary OPC supplementation could alleviate the growth retardation, the decreased activities of glutamic-pyruvic transaminase, glutamic-oxalacetic transaminase, acid phosphatase and alkaline phosphatase and lowered levels of immunoglobulin and complement 3 in serum. With the upregulation of L-cysteine and dihydrouracil involving in cysteine and methionine metabolism, beta-Alanine metabolism, sulfur metabolism, pantothenate and CoA biosynthesis and pyrimidine metabolism in liver, OPC supplementation could alleviate the effects of high level of dietary histamine on growth and serum biochemical parameters. There were no significant difference of growth performance and serum biochemical parameters between HIS group and control group. These results indicated that OPC might act as a potential feed additive to effectively counteract the negative effects of dietary histamine on juvenile American eel.